The Impact of ERP Implementation on the Quality of Accounting Information and Decision Making - Fauzi; Victor Pattiasina; Ulydhatul Ismiyana; Amimah Qodari; Mohammad Aviciena Taufiqurrahman (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of Enterprise Resource Planning (ERP) implementation on the quality of accounting information and managerial decision-making. The development of information technology encourages organizations to adopt integrated systems capable of producing real-time, accurate, and relevant information. ERP, as an integrated information system, is believed to improve the quality of financial reporting through cross-functional data integration, process automation, and strengthening internal controls. Good accounting information quality is ultimately expected to support faster, more accurate, and more rational decision-making processes. This study uses a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to managers and staff involved in the use of the ERP system. The data analysis technique used multiple regression to test the direct influence between variables. The results show that ERP implementation has a positive and significant effect on the quality of accounting information. In addition, the quality of accounting information also has a positive and significant effect on decision-making. Thus, effective ERP implementation can improve the quality of accounting information and strengthen the effectiveness of decision-making within an organization. This study implies that ERP system optimization needs to be supported by organizational readiness, human resource competence, and management commitment to maximize the strategic benefits of the system.